Argentina : Facing the Challenge of Ageing and Social Security - World Bank (Washington, DC, 2012)
This report, Argentina facing the challenge of ageing and social security, is structured in five parts that follow the introduction and summary of main findings. Part I presents a conceptual framework for decision makers charged with crafting policies for old age income security, and describes the evolution and structure of Argentina's pension institutions. Part II presents the findings of the household empirical analysis using existing surveys and the new data from the ETEEP, including the importance of pensions to household income and poverty, the micro-determinants of coverage, and the viability of other income security strategies for the most vulnerable. Part III focuses solely on policies and programs designed to ensure minimum income and cover poverty in old age, presenting estimates of the fiscal cost of proposals made by the principal actors and stake-holders in the pension reform debate. Part IV examines the main pension policy issues in this debate and places these issues in international context. Part V presents some options for the Government and stakeholders to consider as Argentina enters a more detailed and deliberate phase of defining pension reform.